E-training for Ministry of Finance (MOF) in Putrajaya / Erma Shafiqa Mat Supandi - Mat Supandi, Erma Shafiqa (2015)
Ministry of Finance in Putrajaya currently using manually process which is has been explored by the employees, head department and admin. This study have found that manual process will take time while to get an approval from head department. Moreover the information that got by the employees is not really accurate. This research addresses SDLC models consists of waterfall model, v-shaped model, spiral model and RAD model. From the comparison shown that RAD model is more suitable for fast development system which is called E-Training system. The system consists of three users, which are employees, head department and admin. The employees can apply the training program and get notification. For the head department is to approve the application request and admin to view the applicants that have been approved by the head department, add training program and update the information of training program. This system may help users in the Ministry of Finance in Putrajaya for joining training program that have been managed by the admin. The employees can get accurate information and get approval from the head department timely.